AIR MENGALIR, THE EXPLORATION PROCESS OF DRAWING ON NOVELS - I Wayan Sujana (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
This study aims to write a model of the drawing on a novel exploration process, which has produced thousands of sheets of more visual concept patterns. This model project has been done for twenty years by the author and is continuing. Through intense and consistent expression, the estuary produces an approach to the art. The research problems were finding out the process of flowing water in drawing on Novels, investigating the correlation with automatic drawing, and exploring the types of expressions generated from year to year. Some theories used as the basis were the psychology of art and the method of creating MAL in the exploration process. Collecting data was done through observation, implementation, and literature study. The data analysis model was formal and informal. The results showed that human artists have a subconscious space with the potential to produce visual language. The expression of drawing on novels patterns indicated the transformation of shapes every year.